2005
DOI: 10.1093/ajcn/81.5.1142
|View full text |Cite
|
Sign up to set email alerts
|

Plasma arginine concentrations are reduced in cancer patients: evidence for arginine deficiency?

Abstract: Malignant tumors associated with various degrees of metabolic derangements are all associated with decreased plasma arginine concentrations, even without weight loss. This suggests that decreased arginine availability is a specific feature of the presence of cancer. These disturbances in arginine metabolism could contribute to the cascade of metabolic events leading to cancer cachexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
79
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 18 publications
15
79
2
3
Order By: Relevance
“…Arginine depletion has been previously observed in patients with critical illness (35) or cancer (36). In agreement with data obtained in experimental diabetes (37), our results suggest that insulinmediated euglycemia was associated with greater plasma arginine concentration.…”
Section: Discussionsupporting
confidence: 93%
“…Arginine depletion has been previously observed in patients with critical illness (35) or cancer (36). In agreement with data obtained in experimental diabetes (37), our results suggest that insulinmediated euglycemia was associated with greater plasma arginine concentration.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the reduction directly relates to their being used up as part of the pathophysiology of the disease process contributing to an overall anabolic state. The reduction in arginine also correlates well with the studies done by Yvonne LJ Visser et al, [16] who had reported that arginine metabolism is disturbed in cancer patients. They had found plasma arginine levels to be low in patients with cancer, attributing it to the various degrees of metabolic derangements in malignant condition, even without weight loss.…”
Section: Discussionsupporting
confidence: 89%
“…Several investigators have reported changes in plasma free amino acid (PFAA) profiles in cancer patients Lai et al, 2005;Lee et al, 2003;Maeda et al, 2010;Naini et al, 1988;Norton et al, 1985;Okamoto et al, 2009;Proenza et al, 2003;Vissers et al, 2005;Zhang & Pang, 1992). Despite evidence of a relationship between PFAA profiles and some types of cancer, few studies have explored the use of PFAA profiles for diagnosis because although PFAA profiles differ significantly between patients, the differences in individual amino acids do not always provide sufficient discrimination abilities by themselves Lai et al, 2005;Naini et al, 1988;Norton et al, 1985;Proenza et al, 2003;Vissers et al, 2005).…”
Section: "Aminoindex Technology": Example For Early Cancer Diagnosismentioning
confidence: 99%
“…Despite evidence of a relationship between PFAA profiles and some types of cancer, few studies have explored the use of PFAA profiles for diagnosis because although PFAA profiles differ significantly between patients, the differences in individual amino acids do not always provide sufficient discrimination abilities by themselves Lai et al, 2005;Naini et al, 1988;Norton et al, 1985;Proenza et al, 2003;Vissers et al, 2005). To address this issue, we have studied using diagnostic indices based on PFAA concentrations that compress multidimensional information from PFAA profiles into a single dimension to maximize the differences between patients and controls.…”
Section: "Aminoindex Technology": Example For Early Cancer Diagnosismentioning
confidence: 99%